2021
DOI: 10.1371/journal.pone.0237277
|View full text |Cite
|
Sign up to set email alerts
|

Causal graph analysis of COVID-19 observational data in German districts reveals effects of determining factors on reported case numbers

Abstract: Several determinants are suspected to be causal drivers for new cases of COVID-19 infection. Correcting for possible confounders, we estimated the effects of the most prominent determining factors on reported case numbers. To this end, we used a directed acyclic graph (DAG) as a graphical representation of the hypothesized causal effects of the determinants on new reported cases of COVID-19. Based on this, we computed valid adjustment sets of the possible confounding factors. We collected data for Germany from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 63 publications
(106 reference statements)
1
26
2
Order By: Relevance
“…Therefore, increases in false-positives can covary with actual disease risk when there is a higher abundance of true-positives, although this does not mean that false-positives are trivial ( Surkova et al., 2020 ). Survey-based or internet trend sampling (e.g., Rubin et al., 2010 ; Steiger et al., 2021 ) could be combined with epidemic data to provide real-time measures of the dynamics modeled here. Our model, however, can represent a diversity of real-world systems, as socio-cultural dynamics may impede or enhance awareness, reassurance, and social norms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, increases in false-positives can covary with actual disease risk when there is a higher abundance of true-positives, although this does not mean that false-positives are trivial ( Surkova et al., 2020 ). Survey-based or internet trend sampling (e.g., Rubin et al., 2010 ; Steiger et al., 2021 ) could be combined with epidemic data to provide real-time measures of the dynamics modeled here. Our model, however, can represent a diversity of real-world systems, as socio-cultural dynamics may impede or enhance awareness, reassurance, and social norms.…”
Section: Discussionmentioning
confidence: 99%
“…Case counts contribute to the reporting of epidemiological information, which can generate concern regarding disease spread among the population being reported on and encourage the use of protective behaviors. Disease surveillance and subsequent reporting can thereby indirectly mitigate outbreaks by generating public awareness of disease transmission ( Rubin et al., 2010 ; Steiger et al., 2021 ). Such concern can influence wider decision-making within communities, since people aware of increased risk may be more likely to adopt or adhere to protective behaviors that reduce their likelihood of acquiring or transmitting infection ( Wise et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The opposite relation has also been reported [26,27], as well as there being no relations at all [28][29][30][31]. Steiger [21] showed that weather, especially temperature (which has a reducing effect on case numbers) and rainfall (which increases case numbers) affects the reported number of SARS-CoV-2 infections. This study aimed to investigate the spatial patterns of COVID-19 cases (SARS-CoV-2 infected, fatal, and recovered) and the effects of climate and bioclimate on observed changes in infected cases at the state and county levels in Poland.…”
Section: Methodsmentioning
confidence: 96%
“…The opposite relation has also been reported [26,27], as well as there being no relations at all [28][29][30][31]. Steiger [21] showed that weather, especially temperature (which has a reducing effect on case numbers) and rainfall (which increases case numbers) affects the reported number of SARS-CoV-2 infections.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation